Client interpersonal impacts as mediators of long-term outcome in cognitive-behavioral therapy integrated with motivational interviewing for generalized anxiety disorder. (2nd November 2018) - Constantino, Michael J.; Romano, Felicia M.; Coyne, Alice E.; Westra, Henny A.; Antony, Martin M.
Abstract: Objective: A recent trial of generalized anxiety disorder treatment (Westra, H. A., Constantino, M. J., & Antony, M. M. (2016). Integrating Motivational Interviewing With Cognitive-Behavioral Therapy for Severe Generalized Anxiety Disorder: An Allegiance-Controlled Randomized Clinical Trial. Journal of Consulting and Clinical Psychology, 84, 768–782. doi:10.1037/ccp0000098 ) revealed that cognitive-behavioral therapy (CBT) integrated with motivational interviewing (MI) outperformed CBT alone across a 12-month follow up. The present study examined whether this treatment effect was mediated by MI-CBT clients engaging over time in during-session interpersonal behaviors reflecting more friendly dominance, or agentic actions, and less friendly submissiveness (FS), or trustingly compliant actions both theory-specific MI mechanisms.Method: Clients received 15 sessions of MI-CBT ( n  = 42) or CBT alone ( n  = 43). Therapists rated client interpersonal behavior following five sessions, and clients rated their worry at baseline, each session, and 6- and 12-month follow up. Mediator and outcome variables were derived from multilevel models. Mediation was tested using a bootstrapping procedure.Results: There was a significant indirect effect for FS. As expected, CBT clients evidenced greater increases in FS than MI-CBT clients, which in turn, though unexpectedly, related to lower 12-month worry. However, long-term CBT outcomes remained inferior to MI-CBT outcomes even with CBT clients'greater increase in FS.Conclusions: Results suggest that CBT outcomes are more positive when clients trustingly comply; however, MI-CBT remained superior, but for as yet unexplained reasons.